The effects of theoretical models of materials and die on finite element predictions in a forging process of aluminum scroll. (April 2021) - Song, HN; Kim, YS; Joun, MS
In this paper, the effects of theoretical models of materials and dies on finite element (FE) predictions of a hot forging process are presented, to provide process design engineers and researchers with some useful insight into the theoretical approaches on which they rely. The material was assumed to be rigid-viscoplastic or rigid-thermoviscoplastic and the dies were assumed to be rigid or elastic. The problem of die fracture occurring during the hot forging of aluminum fixed scroll was studied. This process is particularly sensitive to theoretical models, mostly because the die-stress component causing the die fracture has a relatively weak relationship with the forming load. A fully thermo-mechanically coupled FE analysis considered die elastic deformation and was first conducted to reveal die fracture with emphasis on the maximum die stress and forming load. The predictions for four simulated cases using different theoretical assumptions of the material and die were then compared. These were also compared with experiments, undertaken to observe the relationship between maximum die stress component and forming load, to reveal the effects of material and die models in FE predictions. The differences in forming load, die stress and their variation with time among the four cases were clarified quantitatively for different die and material models, to provide some insight into metal forming for engineers and researchers.